Dual-functionalized liposome by co-delivery of paclitaxel with sorafenib for synergistic antitumor efficacy and reversion of multidrug resistance. (1st January 2019) - Lei, Meng; Ma, Guanglan; Sha, Sijia; Wang, Xueyuan; Feng, Haiting; Zhu, Yongqiang; Du, Xiao
Abstract: Multidrug resistance (MDR) remains one of the major reasons for inefficiency of many chemotherapeutic agents in cancer therapy. In this study, a D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) and polylysine-deoxycholic acid copolymer (PLL-DA) co-modified cationic liposome coating with hyaluronic acid (HA) was constructed for co-delivery of paclitaxel (PTX) and chemosensitizing agent, sorafenib (SOR) to treat the MDR cancer. The multifunctional liposome (HA-TPD-CL-PTX/SOR) presented good stability against rat plasma and was capable of reversing surface zeta potential under acidic conditions in the presence of HAase. Additionally, experimental result confirmed that the PLL-DA copolymer would facilitate the endo-lysosomal escape of the liposome. In vitro study demonstrated that HA-TPD-CL-PTX/SOR could significantly enhance drug accumulation in resistant MCF-7/MDR cells by inhibiting the P-gp efflux, and effectively inhibited growth of tumor cells. Furthermore, the liposome showed an enhanced anticancer activity in vivo, with a tumor growth inhibition rate of 78.52%. In summary, HA-TPD-CL-PTX/SOR exhibited a great potential for effective therapy of resistant cancers by combining with chemotherapeutic agents and could be a promising nano-carrier for reversing MDR and improving the effectiveness of chemotherapy.